MODERN RESORT HOTELS IN SYRIA: ARCHITECTURE FEATURES AND POSSIBILITIES FOR INNOVATION - D. Yousef (Наука и техника)
The paper explores conditions and possibilities for innovation activity in the field of architecture of Syrian hotels. A concept of “innovation” applied to architectural activity has been analyzed in the paper. Hitherto there is no unequivocal interpretation of effects due to innovation activity not only in respect of hotel architecture but also in respect of architecture as a whole and it concerns urban planning, climatic and socioeconomic conditions of Syria. Factors determining innovative development represent natural, industrial, scientific and technical, technological and other resources. An effort to avoid outof-date design solutions, requirements in development and growth of economic and social living standards can be considered as a driving force for qualitative development of hotel architecture in the resort areas of Syria. Prior to outbreak hostilities in the country the economic and social living standards have been achieved commonly due to high tourist activity. Naturalclimatic and historical potential of Syria contribute to an increase of tourist flows and quantitative composition of hotels. So the purpose of the paper is to reveal the possibilities for qualitative development of new architecture in respect of resort hotels, as the most required hotels by tourists in Syria. It is an obvious fact that architecture of hotels should not only reflect traditions and culture of the region, but it must be also technically modern in order to satisfy a global principle of sustainable development.